Global Well-Posedness for Coupled System of mKdV Equations in Analytic Spaces - Khaled Zennir; Aissa Boukarou; Rehab Nasser Alkhudhayr (Journal of Function Spaces)
The main result in this paper is to prove, in Bourgain type spaces, the existence of unique local solution to system of initial value problem described by integrable equations of modified Korteweg-de Vries (mKdV) by using linear and trilinear estimates, together with contraction mapping principle. Moreover, owing to the approximate conservation law, we prove the existence of global solution.